2011
DOI: 10.1002/ca.22001
|View full text |Cite
|
Sign up to set email alerts
|

Role of the long head of the biceps brachii muscle in axial humeral rotation control

Abstract: This anatomical and biomechanical study focuses on the specific influence of the long head of biceps brachii muscle in controlling axial humeral rotation. The tendon of the long head of the biceps brachii (biceps tendon) is shown to either facilitate or restrict axial humeral rotation. Its effect on axial humeral rotation is strongly related to firstly the amount of biceps tendon load, secondly glenohumeral scapular plane elevation, and thirdly the rotatory position of the humerus. At 0° glenohumeral elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Since both LHBT tenodesis and tenotomy eliminate any effect stabilizing the shoulder, similar results can be obtained after the two procedures. [ 28 - 30 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both LHBT tenodesis and tenotomy eliminate any effect stabilizing the shoulder, similar results can be obtained after the two procedures. [ 28 - 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Since both LHBT tenodesis and tenotomy eliminate any effect stabilizing the shoulder, similar results can be obtained after the two procedures. [28][29][30] Recently, it has been found by postoperative magnetic resonance imaging (MRI) that the incidence rate of rotator cuff retear has no significant difference after LHBT tenodesis and tenotomy. In a prospective randomized-controlled trial, Lee et al [31] found through MRI at 12 months after the operation that 80.4% of the biceps tendon was still in the bicipital sulcus in the tenotomy group.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“… 8 It has been reported that patients who underwent rotator cuff repair with biceps tenodesis showed earlier pain relief than patients without LHBT treatment. 9 On the other hand, it has been reported that LHBT works as a stabilizer of the humeral head 10 , 11 and that loss of LHBT was associated with a small increase in superior translation of the humeral head. 12 According to these findings, we have been preserving the LHBT only when a shoulder with a medium-sized or smaller tear showed no hypertrophy of the extra-articular LHBT and no or mild vascularity in the bicipital groove on preoperative ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…Testing was performed at room temperature, and desiccation was prevented by treating the specimens with 0.9 % saline. The tendons were preloaded to 10 N and then underwent cyclic loading between 10 and 60 N for 200 cycles at 1 Hz [4, 13, 41, 42, 50]. An axial load was then applied at 1 mm/s until failure.…”
Section: Methodsmentioning
confidence: 99%